COLLABORATIVE GOVERNANCE DALAM PEMBANGUNAN KAWASAN PERDESAAN (Tinjauan Konsep dan Regulasi) - Febrian, Ranggi Ade (WEDANA: Jurnal Kajian Pemerintahan, Politik dan Birokrasi, 2015)
Law No. 6 of 2014 About Village in Article 83 (1) describes the Rural Area Development is a mix between the village development within 1 (one) Regency/City. Rural Area Development held in an effort to speed up and improve the quality of service, development, and community empowerment Villages in Rural Areas through participatory development approach. The involvement of various stakeholders in the development of rural areas have the potential to advance collaboration village by clicking its resources. Collaboration begins from the development plan discussed by the Central Government, Provincial Government, District Government / City and Village Government contrary from the village to the national level through a consensus. Problems that occur in this context the views from the concept of Collaborative Governance is the lack of system contexs is apparent from the changes in the legislation, drivers are seen from the elements of leadership which strongly influence development planning in the village, and the dynamics of collaboration that occurred unfavorable conditions all parties resulting sectoral ego. The concept of Collaborative Governance as an alternative base considered able to realize the acceleration and implementation of rural areas as a solution for those who will develop and implement rural areas in the form of policy or research.